2003
DOI: 10.1248/jhs.49.459
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Generation Sublethal Assay of Phenols Using the Nematode Caenorhabditis elegans

Abstract: The nematode Caenorhabditis elegans (C. elegans) was used for a multiple-generation toxicity bioassay of phenols. We examined the sublethal toxicity (fecundity and reproduction) of bisphenol A (BisA), 4-(1-adamantyl) phenol (Adp), and 4,4′-(1,3-adamantanediyl) diphenol (AdDP) over five generations using a Nematode Growth Medium (NGM) 1.7% agar plate. In the fourth generation, the phenols affected the fecundity rate of C. elegans at doses 100-to 10000-fold lower than the LC 50 s. In particular, at 1 nM BisA, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 20 publications
(18 reference statements)
2
24
0
Order By: Relevance
“…Because of the shorter exposure time, phenanthrene concentrations in adults from the first generation (P) were somewhat lower than concentrations in animals from the next generations (F1, F2, F3, F4). Adults from the fourth generation (F3) exposed to the highest remaining phenan- threne concentration in the soil (163 µmol/kg dry soil), which became extinct, showed the highest internal phenanthrene concentration (3.46 µmol PHT/g WW) and the highest BSAF (14). Phenanthrene concentrations and BSAFs for the tenth generation were lowest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the shorter exposure time, phenanthrene concentrations in adults from the first generation (P) were somewhat lower than concentrations in animals from the next generations (F1, F2, F3, F4). Adults from the fourth generation (F3) exposed to the highest remaining phenan- threne concentration in the soil (163 µmol/kg dry soil), which became extinct, showed the highest internal phenanthrene concentration (3.46 µmol PHT/g WW) and the highest BSAF (14). Phenanthrene concentrations and BSAFs for the tenth generation were lowest.…”
Section: Resultsmentioning
confidence: 99%
“…For each generation, actual phenanthrene concentrations in the soil were determined at the beginning, halfway (day 14), and at the end of the exposure period (day 28/35) by Soxhlet extraction followed by high performance liquid chromatography (HPLC). Approximately 13 g of soil were mixed with an equal amount of anhydrous sodium sulfate and extracted for five hours using hexane (HPLC grade, Biosolve, Valkenswaard, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that the reproductive parameters were the most sensitive and the offspring daphnids seemed unadapted to the target compound. Further available studies on multigenerational exposure of organic compounds have shown that the toxic effect, especially in reproduction, tended to be intensified with increasing generation number (Nash et al 2004;Tominaga et al 2003). On the other hand, there have been several studies showing opposite reversed trend relating to reproduction in a multigenerational study.…”
Section: Reproductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Previous studies demonstrated that the use of 1.7% agar Nematode Growth Medium (NGM) plates and C. elegans permits multi-generation sublethal toxicity testing of chemicals that are poorly soluble in water. 10) In this study, we investigated the lethal and sublethal effects of some kinds of perfluoro organic compounds on C. elegans.…”
Section: Introductionmentioning
confidence: 99%